Soil pH mediates the impact of pesticides on bacterial communities, diversity, and abundance - Némethová, Ema; Řezáč, Milan; Gryndler, Milan; Abeyawardana, Oushadee A. J.; Řezáčová, Veronika (Frontiers in Microbiology, 2026)
IntroductionPesticides are widely used in agriculture, yet their non-target effects on soil microbial communities remain poorly understood. This study investigates the short-term impact of five herbicides and three fungicides used for the protection of legumes on the composition and diversity of soil bacteria, with special focus on rhizobia.MethodsUsing three distinct soils from ecologically maintained fields, we assessed changes in bacterial communities and total bacterial abundance in response to different active substances under controlled conditions, 2 weeks after pesticide application. Bacterial diversity was analyzed by amplifying and sequencing the V4 region of the 16S rRNA gene via Illumina paired-end amplicon sequencing. Real-time PCR was used to assess total abundance of bacteria.ResultsOur results show that pesticide effects on bacteria are highly context-dependent, influenced significantly by soil and pH. Significant changes in bacterial diversity were detected only in one soil, whereas in another soil no significant differences among individual pesticides and the untreated control were found. In this soil, particularly the CORUM and pendimethalin-based products, Stomp 400 SC and Sharpen 40 SC, consistently reduced bacterial diversity, while some pesticides had a neutral effect. Rhizobial diversity remained largely unaffected, suggesting greater resilience compared to general bacterial communities. Regarding bacterial community composition, only some pesticides significantly affected bacterial community structure in each soil, and the pesticides showing this effect differed among soils. Redundancy analysis revealed that pH was a stronger driver of bacterial community structure than soil type or pesticide identity, explaining over 60% of community variability.ConclusionThese findings highlight the complex interactions between pesticides, soil characteristics, and microbial communities. Our results support considering soil pH when selecting pesticides to support sustainable soil management and minimize ecological disruption.